FORMATION OF THE ROLE AND PSYCHOLOGY OF YOUTH IN THE CREATION OF A NEW ENLIGHTENED SOCIETY OF UZBEKISTAN - Tashpulatov Abdulaziz Kuvandykovich (Galaxy International Interdisciplinary Research Journal, 2022)
This article discusses the establishment of an enlightened society in the Republic of Uzbekistan, an independent and democratic country, and the many opportunities created for young people. It also details the current state of science, technology, and the renewal of decrees and resolutions in a timely manner and their introduction to the general public.